Mercy to the Worlds: A Universal Message and Its Contemporary Meaning (A Scholarly Study): https://doi.org/10.5281/zenodo.16842203 - Nazia D/O Mohmand; Dr. Naseem Akhter, (Dialogue Social Science Review (DSSR), 2025)
This research paper undertakes an examination of the concept of the Prophet Muhammad ﷺ being Mercy to the Worlds (Rahmat-ul-lil-‘Aalameen) as presented in the Quran and the Hadith, and through the lens of valid Seerah literature, considering its role in the modern world as a significant element of consideration. The paper commences by examining linguistically and terminologically the terms Rahmah and lil-lAlameen, then argues on the universality of the mercy of the Prophet- enveloping not only human beings but also prophets and angels, jinn, hypocrites and disbelievers. The paper also examines his mercy towards his wives, enemies, slaves, along with the animals, and even towards the people who offended him. Based on verses of the Quran and the traditions of the Prophet, the paper points out the components of compassion, justice, and service to humanity that lie in his life. This study draws the inference that the life of the Prophet ﷺ is a universally valuable discourse in interreligious harmony, social fairness, and international peace and as such is so much as pertinent a code of ethics in modern times. Keywords: Rahmat-ul-lil-Alameen, Mercy, Prophet Muhammad (PBUH), Muslims, Non-Muslims Humanitarian, Contemporary Times